STRATEGI PENGUATAN SISTEM PELATIHAN DAN PENILAIAN KINERJA BERBASIS HUMAN CAPITAL UNTUK PENGEMBANGAN KARIR YANG BERKELANJUTAN - Hilma Harmen; Anggi Siva Kagita; Delila Lumban Raja; Kelvin Klementin; Natasyah Yolanda; Navira Vianda; Nopita Andiny; Zaskia Maghfirah Ramadhani Siregar (Relawan Jurnal Indonesia, 2026)
This study examines the importance of strengthening the employee training and performance appraisal system at PT Bank Mandiri in the Depok area based on human capital in supporting sustainable employee career development in an era of intense global and digital competition. Using a qualitative approach with a literature study method, this research collects and analyzes secondary data from scientific journals, books, and other relevant sources, particularly those related to the corporate context at PT Bank Mandiri in the Depok area. The results show that the implementation of a human capital-based training and assessment system, which includes the development of technical skills, soft skills, and evaluation through key performance indicators (KPIs), has a significant impact on increasing productivity, employee retention, and career sustainability. However, challenges such as the lack of technological adaptation in training are major obstacles. The research conclusion emphasizes that the human capital approach is an effective strategy for improving individual competence and organizational resilience, with recommendations to integrate digital technology into training and performance appraisal systems.